The impact of interhospital transfer on mortality benchmarking at Level III and IV trauma centers: A step toward shared mortality attribution in a statewide system. Issue 1 (January 2020) - Holena, Daniel N.; Kaufman, Elinore J.; Hatchimonji, Justin; Smith, Brian P.; Xiong, Ruiying; Wasser, Thomas E.; Delgado, M. Kit; Wiebe, Douglas J.; Carr, Brendan G.; Reilly, Patrick M.
Abstract : BACKGROUND: Many injured patients presenting to Level III/IV trauma centers will be transferred to Level I/II centers, but how these transfers influence benchmarking at Level III/IV centers has not been described. We hypothesized that the apparent observed to expected (O:E) mortality ratios at Level III/IV centers are influenced by the location at which mortality is measured in transferred patients. METHODS: We conducted a retrospective study of adult patients presenting to Level III/IV trauma centers in Pennsylvania from 2008 to 2017. We used probabilistic matching to match patients transferred between centers. We used a risk-adjusted mortality model to estimate predicted mortality, which we compared with observed mortality at discharge from the Level III/IV center (O 1 ) or observed mortality at discharge from the Level III/IV center for nontransferred patients and at discharge from the Level I/II center for transferred patients (O 2 ). RESULTS: In total, 9, 477 patients presented to 11 Level III/IV trauma centers over the study period (90% white; 49% female; 97% blunt mechanism; median Injury Severity Score, 8; interquartile range, 4–10). Of these, 4, 238 (44%) were transferred to Level I/II centers, of which 3, 586 (85%) were able to be matched. Expected mortality in the overall cohort was 332 (3.8%). A total of 332 (3.8%) patients died, of which 177 (53%) died at the initial Level III/IV centers (O 1 ). Including posttransfer mortality for transferred patients in addition to observed mortality in nontransferred patients (O 2 ) resulted in worse apparent O:E ratios for all centers and significant differences in O:E ratios for the overall cohort (O 1 :E, 0.53; 95% confidence interval, 0.45–0.61 vs. O 2 :E, 1.00, 95% confidence interval, 0.92–1.11; p < 0.001). CONCLUSION: Apparent O:E mortality ratios at Level III/IV centers are influenced by the timing of measurement. To provide fair and accurate benchmarking and identify opportunities across the continuum of the trauma system, a system of shared attribution for outcomes of transferred patients should be devised.